(3MGTjI GdSjO GdTQja Ydi TQM GdWhGdYs - (3Ydj Hf eMeO Hf Ydj, GdeYQha HGdTQja GdLQLGfj,J (B816 (3g` s; (3GdCUagGfjs
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje hHg fSJYjf bhdg HMSH GdEQGOI Hg dG HEYJHGQ Cf GdbOQI YdI JGeI dJNUjU Pdc GdHYV dCfg dh cGf cPdc jdRe EfJgGA GdbOQI ai Pdc GdHYV s
(3BNQgG (B:s
(3hdeG cGf ef Shi GdHGQi eY GdNdb hGdbOQI hGddg CYde HGdUhGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B3s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3Gdabg GdESdGejs